Organización documental y su incidencia en la calidad académica de la Universidad Técnica de Babahoyo Extensión Quevedo año 2015. - García Duarte, Karem Silvana (2016)
The research project has been carried out has components that can not be ignored when tending to draw general conclusions that interest us. The investigation was preceded by methodological elements that sometimes mistook the development of the search for a solution to the problem. We can conclude that there are indeed contradictory elements in the documentary organization process in the Educational Quality of the Technical University of Babahoyo Extension Quevedo that we have the obligation to take over as the new elements that appear as results of observation and analysis that has been taken. One of the conclusions we can draw from this research is necessary to optimize the use of information using standards and documentary procedures allowing documentary organization of the archives of the Technical University of Babahoyo Extension Quevedo, there is no perfect organization but is They take into account the diversity of needs that may exist and the characteristics and related to the development of the documentary organization. It is however to find the maximum response, and the best solutions when confronting a design document organization.